Confidentiality and HIV/AIDS in South Africa - Uys, Leana R (Nursing ethics, 2000)
Keeping the diagnosis of a client confidential is one of the cornerstones of professional practice. In the case of a diagnosis such as HIV/AIDS, however, the ethics of this action may be challenged. Such a decision has a range of negative effects, for example, the blaming of others, supporting the denial of the client, and complicating the health education and care of the patient. It is suggested that the four ethical principles should be used to explore the ethics of such decisions, and that professional regulatory bodies and organizations should support professionals in situations where the client’s sexual partner is informed against the wishes of the client.